Modelagem matemática do processo de extração supercrítica de Humulus lupulus L. com CO2 - Kupski, Sergio Carlos (2015)
Supercritical fluid extraction (SFE) process of vegetable oils with CO2 is an alternative to the traditional processes, with advantages related to final product quality, extraction yield and simpler separation stages. Hops (Humulus Lupulus L.) are widely used for beer brewing and their essential oils contain substances with potential pharmaceutical use. Mathematical modeling of the mass transfer mechanisms that rule the SFE may provide information about the process parameters influence on the total yield and extraction rate. This work intends to analyze the influence of the following parameters: temperature (de 35 a 55º C), pressure (100 a 200 bar), particle size (de 3,28 X 10-4 m a 1,02 X 10-3 m), particle size distribution and raw material treatment. Extraction of hop with supercritical carbon dioxide was performed on experimental scale. The data obtained was used to adjust the extraction curves simulated with five models available at literature. Besides those, the data allowed to test a proposed model, applied for the extraction from hop bracts. Tested models adjusted the experimental data satisfactorily and the estimated parameters analysis allowed building another model.